Pengaruh Penambahan Plastik Tipe PET (Polyethylene Terepthalete) Terhadap Campuran Laston AC-WC - Rahayu, Putri; Rifqi, Mirza Ghulam; Amin, M. Shofi’ul (Journal of Applied Civil Engineering and Infrastructure Technology, 2021)
To find a solution the road problem in Indonesia, it requires to perform a modified mixture to obtain good quality of asphalt concrete pavement with addition the new material. The new material as an additive to increase the quality of pavement is a Polyethylene Terepthalete (PET). This Research uses some variation as: 4%, 4,5%, and 5% of PET from weight of asphalt concrete. The purpose of this research is to identify the impact of PET as an additive in asphalt concrete wearing course (AC-WC). The metodh used in this study is a dry process from some references (such as: design and implementation of asphalt pavement used plastic waste, 2019). The result of marshall test found that the optimum performance and stability for 5% PET with 6.5% variances value of asphalt bitumen. Stability of five variation averange is 2193.3 kg; Flow is 3.90 mm; Void in Mix (VIM) is 3.7%; void mix in aggregate (VMA) is 16,7%; Void filled Bitumen (VFA/VFB) is 77.9%, and Marshall Quotient is 562,4 kg/mm. By the references used in this research, these value have been suitable with the research result from those references. It can be concluded that the asphalt pavement with using an additive of PET gives better performances and stability than without PET.